PELAYANAN INFORMASI PADA SITUS DI KANTOR DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KOTA SINGKAWANG - Hendra Juliardi E.01110017 (FISIP Universitas Tanjungpura, 2014)
The goal of this research is to discover and analyze the Description of the Quality of the Information Attendance on the Site Office of Transportation, Communication, and Informatics Department in giving attendance satisfaction based on the indicator that is Tangibles, Reliability,Responsive, Assurance and Empathy. The problem is in the some parts of menu on Dishubkominfo’s site of Singkawang City do not contain the information and the information attendance on the Dishubkominfo’s site of Singkawang City doesn’t fulfil the Operational Standard of Public Information Service Procedure in the Governmental Environment of Singkawang City. This research uses qualitative research method with descriptive research model. The result of this research shows that the five indicators have the problem, that is (1) Tangible: the physical facility side in the form of the internet connection is very slow in the certain time, (2) Reliability: the quantity of Human Resources that is limited and the information on the menu, sub menu and subs menu do not contain the information and also the unclear main person in charge that handle this stuff, (3) Responsive: the unseen of the responsiveness on the site, (4) Assurance: there is no guarantee about the contain of the information, accuracy and time speed, (5) Empathy: the existence of different practice of the empathy from the Dishubkominfo’s side of Singkawang City with the site visitors’ expectations. Then the focus of the researcher’s suggestion is on the indicators of Reliability that is Dishubkominfo of Singkawang City should propose again and seek the additional quantity of human resources (HR) that is balanced by the adequate quality of Human Resources (HR), Section Staff of Means of Communication and Information Dissemination (SKDI) could fill in the information on all the menus and sub-menus that are available on the website of Dishubkominfo of Singkawang City and the Head of Communications and Information Technology could improve the coordination with the EDP (Electronic Data Management) so that there is a clear division of tasks and their publication on the site so that there is full responsibility for the tasks respectively without any reason throwing responsibility each other. Keywords: The Quality of Information Attendance, Site, Transportation, Communication, and Informatics Department, Singkawang City